2009
DOI: 10.1007/s00439-009-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies in ADHD

Abstract: Attention-deficit/hyperactivity disorder, ADHD, is a common and highly heritable neuropsychiatric disorder that is seen in children and adults. Although heritability is estimated at around 76%, it has been hard to find genes underlying the disorder. ADHD is a multifactorial disorder, in which many genes, all with a small effect, are thought to cause the disorder in the presence of unfavorable environmental conditions. Whole genome linkage analyses have not yet lead to the identification of genes for ADHD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
327
1
22

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 378 publications
(361 citation statements)
references
References 172 publications
(355 reference statements)
11
327
1
22
Order By: Relevance
“…60,63,64 Although several genes affected by CNVs identified in this study contain SNPs that yield significant signals in GWA studies, there is presently no obvious relationship between the heritability of ADHD and the number or strength of the observed effects. Unlike rare CNVs, common variants for ADHD may be of very small effect and thus require very large samples to be reliably detected.…”
Section: Discussionmentioning
confidence: 84%
“…60,63,64 Although several genes affected by CNVs identified in this study contain SNPs that yield significant signals in GWA studies, there is presently no obvious relationship between the heritability of ADHD and the number or strength of the observed effects. Unlike rare CNVs, common variants for ADHD may be of very small effect and thus require very large samples to be reliably detected.…”
Section: Discussionmentioning
confidence: 84%
“…Combined, they explain less than 10% of variance (Franke, Neale, & Faraone, 2009). This means they occur only slightly more often in diagnosed individuals than in controls, and they do not explain nor predict ADHD behaviours.…”
Section: The Genetic Origins Of Adhd May Be Overestimatedmentioning
confidence: 99%
“…Linkage studies elicited several loci likely containing rare genetic variants of major effect only present in single large families, but also common variants of smaller effect present across several families [92]. In addition, genome-wide association studies indicated a very limited number of common variants of small effect to date [33,62].…”
Section: Introductionmentioning
confidence: 99%